2019
DOI: 10.32734/ijnpc.v1i1.963
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Anemia in Patient With Nasopharyngeal Carcinoma at Ent-HNS Department West Nusa Tenggara

Abstract: Article InfoIntroduction: Nasopharyngeal carcinoma is common in China and Southeast Asia, including Indonesia. The cases are often diagnosed in an advanced stage with a poor prognosis. Objective: The purpose of this study was to determine the incidence of anemia in nasopharyngeal carcinoma patients in the ENT-HNS Department West Nusa Tenggara Hospital. Methods: the methods of this research are a descriptive study that used data from the medical record of West Nusa Tenggara Hospital. The data were obtained betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…Hemoglobin of less than 14 mg/dL was found in 86.61% of the participants. This result was consistent with a prior study conducted by Susilawati that 87.5% of patients with NPC had anemia [16]. A study in China reported that hemoglobin level less than 11g/dL significantly lowers the Overall Survival (OS) in NPC (70% vs. 78%).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Hemoglobin of less than 14 mg/dL was found in 86.61% of the participants. This result was consistent with a prior study conducted by Susilawati that 87.5% of patients with NPC had anemia [16]. A study in China reported that hemoglobin level less than 11g/dL significantly lowers the Overall Survival (OS) in NPC (70% vs. 78%).…”
Section: Discussionsupporting
confidence: 92%
“…Malignancy anemia is caused by several factors such as malnutrition, malabsorption, acute/chronic bleeding, inflammation, metastatic infiltration to bone marrow, and myelosuppression due to cancer therapy [18]. Susilawati also reported that hypochromic microcytic anemia is the most common type in NPC patients, associated with iron deficiency anemia [16]. In patients with malignancy, tumor cells induce the secretion of serotonin and bombesin, resulting in appetite suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, environmental substances such as Epstein-Barr Virus, alcohol, cigarettes, salted foods, canned foods, traditional medicines, formaldehyde, wood dust, and non-environmental risk factors such as gender and ethnicity have been determined as risk factors for nasopharyngeal carcinoma. [8][9][10][11] Being an Asian is a risk factor for nasopharyngeal carcinoma due to the narrower structure of the nasopharynx compared to other ethnicities. Therefore, repeated infections can occur and lead to malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…According to epidemiological studies, the average latent period of cancer is 15 years or more. 3,11,14 Thus, when calculated with the latent period, it can be assumed that exposure begins from adolescence to young adulthood. Undergraduate students are one of the groups belonging to adolescence and young adulthood.…”
Section: Introductionmentioning
confidence: 99%